Gut microbiota in early pregnancy among women with Hyperglycaemia vs. Normal blood glucose - Beibei Gao; Mengdan Zhong; Qiong Shen; Ying Wu; Mengdie Cao; Songwen Ju; Lei Chen (BMC, 2020)
Abstract Background Recent studies suggest that there is a link between the gut microbiota and glucose metabolism. This study aimed to compare the gut microbiota during early pregnancy of women with hyperglycymia to those with normal blood glucose. Methods Gut microbial composition was analysed in 22 women with hyperglycaemia and 28 age-matched healthy controls during their first prenatal visits (< 20 weeks) using high throughput sequencing of the V3-V4 region of the 16S ribosomal RNA gene. Hyperglycemia was diagnosed based on the criteria recommended by the International Association of Diabetes and Pregnancy Study Groups in 2010. Results Women with hyperglycemia in pregnancy (HIP) had significantly lower microbial richness and diversity compared with healthy pregnant women. The proportions of the Firmicutes and Bacteroidetes phyla and the ratio of Firmicutes:Bacteroidetes were not different between the two groups. We observed that individuals with HIP had an increased abundance of Nocardiaceae, Fusobacteriaceae, etc., whereas healthy controls had significantly higher levels of Christensenellaceae, Clostridiales_vadinBB60_group, Coriobacteriaceae, etc. Similarly, levels of the members of the Ruminococcaceae family, including Ruminococcaceae_UCG-014, Ruminococcaceae_UCG-003, and Ruminococcaceae_UCG-002, were significantly reduced in the HIP group and were negatively correlated with HbA1c. HbA1c levels were positively correlated with Bacteroidaceae and Enterobacteriaceae and negatively correlated with Christensenellaceae, etc. CRP was positively correlated with the Bacteroidaceae and Fusobacteriaceae families and the Fusobacterium genus. Conclusions Our study revealed that individuals with HIP have gut microbial dysbiosis and that certain bacterial groups are associated with glucose metabolism during pregnancy. Further study is needed to provide new ideas to control glucose by modifying the gut microbiota.